Removal of heavy metals by activated carbons prepared from hydrothermally treated biomass with phosphoric acid treatment / Ganiyu Abimbola Adebisi - Ganiyu Abimbola , Adebisi (2017)
The production of adsorbents for heavy metal adsorption from agricultural by-products (waste), is a research area of high interest that deals with solving problems associated with waste disposal as well as producing value added products that can be applied in a number of ways environmentally. In fulfillment of this esteemed objective, this research aimed at developing novel powdered adsorbents (PAC) from banana empty fruit bunch (BEFB), rattan sawdust (RS) and granular activated adsorbent (GAC) from longan fruit shell (LFS). To enhance the adsorption capacities of the activated carbons, the precursors were pre-treated through hydrothermal method followed by chemical activation with phosphoric acid (H3PO4). The results demonstrated that the optimum condition to obtain highest removal percentage and yield were dependent on the characteristics of the raw materials and the adsorbate under investigation. The results of characterization showed significant improvement in the surface area and pore size distribution characteristics of the hydro-char after activation process. BET surface area of BEFBAC and RSAC are 762.05 m2/g and 1151.23 m2/g respectively. The results further reveal maximum adsorption capacity of 82.86%, 61.03% [Pb(II), Zn(II)] and 86.71%, 64.26% [Pb (II), Zn (II)] for BEFBAC and RSAC respectively at the equilibrium conditions (time = 210min, pH = 5.5, temperature = 30oC and initial adsorbate concentration of 350mg/L). This indicated a promising potential in the use of these biomass as precursors for preparing adsorbents for removing heavy metals from wastewaters. Furthermore, the adsorption isotherms and kinetics reveal that the process fitted perfectly into Langmuir isotherm and pseudo-second-order reaction model. The thermodynamics study showed that the adsorption process is endothermic, spontaneous and feasible under the investigated temperatures. The result for longan fruit shell granular activated carbon (LFSAC) indicated that the adsorption capacities for the single solute systems were higher than those obtained for the binary mixture for the two metals. The maximum adsorption capacity for the single solute at different initial concentrations of the adsorbates for Pb(II) and Zn(II) are 80.4% and 59.3% respectively. The adsorption processes were best fitted into the Langmuir isotherm model for both metals. The results were further subjected to pseudo-first-order, pseudo-second-order, intra-particle diffusion and Elovich kinetic models. The result showed that the single solute adsorption data best fitted into pseudo-second-order kinetic model. The adsorption capacity of Pb(II) is higher than that obtained for Zn(II) for the binary system. The percentage removal of the metals in the binary system decreases with increase in the initial concentration of the other metal ion.